The supervisory jurisdiction of the Federal Supreme Court in Iraq - Hussien, Hanaa; Taleb, Musadaq (Journal of Legal Sciences, 2023)
The constitution  occupies the highest rank in the legislative hierarchy, as its rules are considered the highest rules in the entire legal system, and accordingly it follows that the competent authority in legislation respects the constitution and does not violate it, and in other words, the legislation that is issued by it should be constitutional, i. Modern constitutional documents in many countries have organized the issue of creating oversight over the work of those authorities, and this oversight may be judicial when it is exercised by the judiciary, and it may be non-judicial when entrusted to other bodies, and judicial oversight is achieved through an original lawsuit filed to challenge the A law or regulation before a Supreme Constitutional Court, or by referral from Through the subject matter jurisdiction when the constitutionality of a law or regulation is raised on the occasion of a case before the subject matter court, and it can also be achieved by combining the original case with the subsidiary plea, noting that judicial oversight over the constitutionality of legislation is the best method of oversight due to the judiciary’s impartiality. And independence in addition to being away from whims and caprices.